Have You Seen My Teeth? A Case with an Extraordinary Radiologic Finding - (:unkn) unknown (THIEME MEDICAL PUBL INC, 2016)
A 55-year-oldman was admitted to the emergency department with severe dyspnea and hoarseness, starting immediately after a hypotensive syncope attack at home. Pulmonary auscultation revealed generalized stridor and right-sided wheezing, with no finding in the upper airway on direct laryngoscopy. Chest X-ray and computed thorax tomography revealed a high-density foreign body on the carina, causing partial obstruction in the right main bronchus. The fractured dental plate, probably aspirated during the syncope attack, was successfully removed by rigid bronchoscopy. The postoperative period was uneventful and the patient was discharged on the same day. Rapid physical and radiologic examination of patients with severe acute dyspnea is vital for determining the treatment modality and preventing any potential mortality.
Keywords: bronchoscopy; computed tomography; foreign body; trachea; FOREIGN-BODIES; ASPIRATION; MANAGEMENT; TOOTH